Second cycle of intralesional Collagenase Clostridium histolyticum for Peyronie's disease using the modified shortened protocol: Results from a retrospective analysis. (31st January 2020) - Capece, Marco; Arcaniolo, Davide; Manfredi, Celeste; Palmieri, Alessandro; De Sio, Marco; Verze, Paolo; Fusco, Ferdinando; Longo, Nicola; Mirone, Vincenzo
Abstract: The purpose of this study was to evaluate the effectiveness and safety of the second cycle of Collagenase Clostridium histolyticum injections using the modified shortened protocol. We performed a retrospective analysis on patients who had already undergone the first cycle of injections using the modified shortened protocol and requested more injections to improve the remaining curvature. The International Index of Erectile Function, the Peyronie's Disease Questionnaire and the Global Assessment of Peyronie's Disease questionnaire were self‐administered to all patients. All the parameters were recorded at baseline, after the first cycle and after the second cycle of injections. All adverse events were recorded. Seventeen patients completed two cycles of injections. All patients had a reduction of the initial curvature after the first cycle, with a mean improvement of 17.4° (27.4%). After the second cycle, the reduction of the curvature was 7.9° (17.1%), and 29.4% of patients had no further improvement. No severe side effect was recorded. The results of the present study confirm the effectiveness and safety of the modified shortened protocol of Collagenase C. histolyticum injections for Peyronie's disease. However, the second cycle of three injections may be less effective, and patients may not be completely satisfied.